2007
DOI: 10.1111/j.1365-2249.2007.03436.x
|View full text |Cite
|
Sign up to set email alerts
|

Can interferon-γ and interleukin-10 balance be associated with severity of human Leishmania (Viannia) braziliensis infection?

Abstract: Summary Suitable levels of interferon (IFN)-g and interleukin (IL)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
81
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 26 publications
6
81
0
1
Order By: Relevance
“…Although IL-10 can favor the progression of the disease in the early phase of leishmaniasis, depending on the counter balance exerted by IFN-γ, cure can be achieved due to its effector functions on parasitized macrophages (Rocha et al 1999, Bosque et al 2000. Moreover, our results strengthen the idea that the intrinsic ability to produce IL-10 in response to Leishmania infection can be a key factor in avoiding a possible harmful effect of IFN-γ, exerting an important function on regulating inflammatory responses necessary for infection control (Rocha et al 1999, Belkaid et al 2001, Gomes-Silva et al 2007.…”
Section: Discussionsupporting
confidence: 72%
“…Although IL-10 can favor the progression of the disease in the early phase of leishmaniasis, depending on the counter balance exerted by IFN-γ, cure can be achieved due to its effector functions on parasitized macrophages (Rocha et al 1999, Bosque et al 2000. Moreover, our results strengthen the idea that the intrinsic ability to produce IL-10 in response to Leishmania infection can be a key factor in avoiding a possible harmful effect of IFN-γ, exerting an important function on regulating inflammatory responses necessary for infection control (Rocha et al 1999, Belkaid et al 2001, Gomes-Silva et al 2007.…”
Section: Discussionsupporting
confidence: 72%
“…23,24 Therefore, it is an imbalance between pro-inflammatory and regulatory cytokines that leads to ATL pathogenesis. 23,32,33 Herein, we showed that elderly subjects have a decrease in the antigen-response of IFNγ, and thus lack the main cytokine responsible for macrophage activation and killing. Furthermore, we also observed an increase in IL-10 that may facilitate parasite growth.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the extensive tissue damage can be low expression or no modulation of IL-10 mRNA, which has been observed in the majority of tissues of all animals and leads to a decreased ability to downregulate IFN-␥ mRNA. In human leishmaniasis patients, a high IFN-␥/ IL-10 ratio is associated with more severe clinical forms of the disease, such as mucosal leishmaniasis (37,38).…”
Section: Discussionmentioning
confidence: 99%